2019
DOI: 10.1111/jdi.12982
|View full text |Cite
|
Sign up to set email alerts
|

Independent links between plasma xanthine oxidoreductase activity and levels of adipokines

Abstract: Aims/Introduction Xanthine oxidoreductase ( XOR ) is a rate‐limiting enzyme that catalyzes uric acid formation in the purine metabolism, is involved in an increase in reactive oxygen species. Plasma XOR activity has been shown to be associated with obesity, smoking, liver dysfunction, hyperuricemia, dyslipidemia and insulin resistance. Materials and Methods The association between plasma XOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 47 publications
2
27
1
Order By: Relevance
“…Change in body weight may be indirectly associated with change in plasma XOR activity through modulation of hypoxanthine secretion from adipose tissue as a substrate of XOR. Other than liver dysfunction and obesity, plasma activity of XOR is associated with a habit of smoking and the presence of lifestyle-related diseases, including hyperuricemia, hypertension, dyslipidemia and diabetes mellitus [6][7][8][9]. However, in the present study, no significant difference was observed between annual changes in plasma XOR activities in participants with and those without a habit of smoking (Fig.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Change in body weight may be indirectly associated with change in plasma XOR activity through modulation of hypoxanthine secretion from adipose tissue as a substrate of XOR. Other than liver dysfunction and obesity, plasma activity of XOR is associated with a habit of smoking and the presence of lifestyle-related diseases, including hyperuricemia, hypertension, dyslipidemia and diabetes mellitus [6][7][8][9]. However, in the present study, no significant difference was observed between annual changes in plasma XOR activities in participants with and those without a habit of smoking (Fig.…”
Section: Discussioncontrasting
confidence: 62%
“…An accurate assay for plasma activity of XOR in humans has recently been established using triple quadrupole mass spectrometry and liquid chromatography to detect the formation of [ 13 C 2 , 15 [5]. Using this method, we and others have recently demonstrated that plasma XOR activity is a new biomarker of metabolic disorders associated with obesity, insulin resistance, liver dysfunction, hyperuricemia and adipokines [6][7][8][9]. In addition, it has been reported that habitual exercise can decrease plasma XOR activity [10].…”
mentioning
confidence: 99%
“…An accurate and sensitive assay for activity of plasma XOR in humans has been newly developed using liquid chromatography and triple quadrupole mass spectrometry to measure [ 13 C 2 , 15 N 2 ]‐uric acid using [ 13 C 2 , 15 N 2 ]‐xanthine as a substrate. Using this assay, we and others have shown that activity of plasma XOR is a novel metabolic biomarker associated with obesity, insulin resistance, hyperuricemia, liver dysfunction and adipokines. Furthermore, we showed unexpected high activity of plasma XOR in some hyperuricemic patients by using an XOR inhibitor and in some female relatively hypouricemic patients .…”
Section: Introductionmentioning
confidence: 86%
“…FGF21, fibroblast growth factor 21. Circulating FGF21 levels have been reported being related to several risk factors of cardiovascular disease (e.g., increase in blood lipid and glucose 12) , oxidative stress 26) , and inflammation 27) ) and to be higher in hypertensive adults than healthy adults 11) . The present study demonstrated, in middle-aged and older women without hypertension, that serum FGF21 levels were independently associated with aortic BP, particularly aortic PP which is more strongly associated with the risk of cardiovascular disease than peripheral BP 28,29) .…”
Section: Discussionmentioning
confidence: 99%